Investigating the Effect of Islamic Theology on Moderate Attitudes of Muslims - Tri Astutik Haryati; Amat Zuhri; Miftahul Ula; Annisa Mutohharoh (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
Islamic theology is the main doctrine of belief centered on tauhid (the Oneness of God) and forms the foundation of the life of Muslims. The principle of tauhid establishes a framework of relations among nations based on brotherhood which is the essence of true religious life. Therefore, this study aimed to investigate the influence of belief on Muslims' moderate attitude using a correlational survey approach. The statistical population consisted of 2250 students from Islamic Religious Universities (PTKI) in Pekalongan, who have taken the Religious Moderation course. The sample was determined using the accidental sampling technique with 289 students participating as respondents. Data were collected through a psychological scale and analyzed using simple regression analysis. The results showed that belief positively influenced the moderate attitudes of Muslims, accounting for 39.1% of the variance. This study provided a new perspective on Islamic moderation and the influencing factors, emphasizing a comprehensive understanding of Islamic Theology and the implications for attitudes and behaviors of Muslims. It also underscored the importance of internalizing the principles and values of Islamic moderation into da'wah and education. Beyond theoretical insights, the study offered practical guidance for policymakers in designing interventions to address the threats of radicalism and extremism.